KONTRIBUSI CRITICAL THEORY DALAM PERKEMBANGAN STUDI HUBUNGAN INTERNASIONAL DI INDONESIA - Sonny Sudiar; Yuni arti (UNIDA Gontor, 2017)
This article examines the main theoretical contribution of critical theory in analyzing the contemporary of international relations phenomena. Empirical and conceptual applications of critical theory as a perspective in international relations study are discussed. It is argued that critical theory has specific contribution to the development of international relations studies in Indonesia